The orbital kinematics of η Carinae over three periastra with a possible detection of the elusive secondary's motion. Issue 4 (6th January 2023) - Strawn, Emily; Richardson, Noel D; Moffat, Anthony F J; Ibrahim, Nour; Lane, Alexis; Pickett, Connor; Chené, André-Nicolas; Corcoran, Michael F; Damineli, Augusto; Gull, Theodore R; Hillier, D John; Morris, Patrick; et al.
ABSTRACT: The binary η Carinae is the closest example of a very massive star, which may have formed through a merger during its Great Eruption in the mid-19th century. We aimed to confirm and improve the kinematics using a spectroscopic data set taken with the Cerro Tololo Inter-American Observatory 1.5-m telescope over the time period of 2008–2020, covering three periastron passages of the highly eccentric orbit. We measure line variability of H α and H β, where the radial velocity and orbital kinematics of the primary star were measured from the H β emission line using a bisector method. At phases away from periastron, we observed the He ii 4686 emission moving opposite the primary star, consistent with a possible Wolf–Rayet companion, although with a seemingly narrow emission line. This could represent the first detection of emission from the companion.